Trophic Ecology of Juvenile Southern King Crab Associated with Kelp Forest: Evidence of Cannibalism - Pardo, Luis Miguel; Andrade Diaz, Claudia Daniela Yanett; Zenteno-Devaud, Lisette; Garrido, Bastian; Rivera, Cristobal (My University, 2021)
The southern king crab, Lithodes santolla, is a well-known predator/scavenger species during its adult phase but its feeding strategy in early stages is less studied. This information is important to understand their role in ecosystems and to improve fishery management (i.e., stock enhancement). Based on stomach contents and stable isotope analysis, we determined variation in the composition of diet and niche overlap in vagile and cryptic phase collected within and outside a kelp forest, Macrocystis pyrifera, of Aguila Bay at the Magellan Strait in Patagonia, Chile. Results of juvenile stomach content analysis showed 60% dissimilarity between cryptic and vagile juvenile phases. Algae dominated the volumetric contribution in cryptic juveniles while crustacean dominated the diet in vagile phase. Exoskeleton of other king crabs occurred in 43% of juveniles with crustaceans in their stomach. This fact confirms cannibalistic behavior in the wild in this species, which is consistent with findings in massive laboratory cultures. There was no evidence of isotopic niche shift between cryptic and vagile juvenile phases. Overlapping isotopic niches of different-sized juveniles suggest that they exploit similar food resources. However, vagile individuals occupy a higher trophic position than cryptic individuals, which could suggest a switch in dietary preference, from detritivorous/herbivory within kelp forests to omnivory outside of kelp forests, and an increase in the level of cannibalism in vagile juveniles.
Keywords: patagonia; macrocystis; stable isotopes; stomach content; decapoda; lithodes santolla